(untitled) (Research, Society and Development, 2022)
Introduction: Squamous cell carcinoma of the oral cavity (SCC) represents from 90% to 95% of cases of malignant tumors of the mouth, with greater frequency on the tongue, especially on the posterior border, with 95% of its incidence occurring after the 45 years of age, with a tendency of increasing occurrence in young people, under the age of 45, tobacco and alcohol users, which may also be related to systemic factors, such as general malnutrition or anemia. SCC has a different behavior in young patients, corresponding to a more aggressive form of the disease. Objective: To carry out a literature review of articles that report the incidence profile of oral cavity cancer in young patients. Methodology: This is an integrative literature review that used the PubMed, Lilacs and Scielo databases through the keywords registered in the Health Sciences (DeCS), respectively in Portuguese, Spanish and English, selecting scientific articles among the years 2010 to 2022. Results: 409 articles on the topic were identified in the databases used for the research, and after being chosen, 27 articles were used that best adapted to the objectives of the study in question. A predominance of males was found, aged between 17 and 45 years. Conclusion: Young patients who developed the disease have some points in common, such as genetic predisposition and early contact with oncogenic viruses and alcohol and cigarette abuse.